2022
DOI: 10.48550/arxiv.2202.07328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secure Beamforming Design for Rate-Splitting Multiple Access in Multi-antenna Broadcast Channel with Confidential Messages

Abstract: As physical layer security evolves to multi-user systems, multi-user interference (MUI) becomes an unavoidable issue. Recently, rate-splitting multiple access (RSMA) emerges as a powerful non-orthogonal transmission framework and interference management strategy with high spectral efficiency. Unlike most works fully treating MUI as noise, we take all users' secrecy rate requirements into consideration and propose an RSMA-based secure beamforming approach to maximize the weighted sum-rate (WSR), where MUI is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The rate-splitting multiple access (RSMA) approach has been introduced in the literature as a powerful multiple access method aimed at enhancing spectral efficiency, and energy efficiency, particularly in scenarios with both perfect and imperfect Channel State Information at the Transmitter (CSIT) [9]- [17]. RSMA holds promise for addressing the challenges posed by varying channel conditions and interference levels, offering improved performance metrics across a range of wireless communication scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate-splitting multiple access (RSMA) approach has been introduced in the literature as a powerful multiple access method aimed at enhancing spectral efficiency, and energy efficiency, particularly in scenarios with both perfect and imperfect Channel State Information at the Transmitter (CSIT) [9]- [17]. RSMA holds promise for addressing the challenges posed by varying channel conditions and interference levels, offering improved performance metrics across a range of wireless communication scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…RSMA holds promise for addressing the challenges posed by varying channel conditions and interference levels, offering improved performance metrics across a range of wireless communication scenarios. Moreover, it has been shown that RSMA method and AN beamforming are promising solutions to improve the wireless security, especially in the presence of numerous eavesdroppers that may seize from a high transmit power [7], [9]. Particularly, RSMA relies on the rate-splitting technique to divide the message into the private and common parts [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation